SAT0128 ARE THERE ANY DIFFERENCES BETWEEN ADULT-ONSET RHEUMATOID ARTHRITIS PATIENTS AND LATE-ONSET RHEUMATOID ARTHRITIS PATIENTS IN TERMS OF USE OF BIOLOGICAL DRUGS AND DRUG RETENTION RATE? RESULTS FROM THE TURKBIO REGISTRY. (2nd June 2020) - Yazici, A.; Cefle, A.; Dalkiliç, E.; Can, G.; Senel, S.; Koca, S. S.; Inanc, N.; Goker, B.; Yilmaz, S.; Akar, S.; Soysal, O.; Pehlivan, Y.; et al.
Abstract : Background: Rheumatoid arthritis(RA) is one of the most frequent rheumatic disease, and the age of onset is between 30-50 years old. Late-onset RA(LORA) is usually defined as RA with onset at age 60 or over. Objectives: To investigate the choice, effectiveness and the retention rate of biological drugs in LORA patients. Methods: TURKBIO registry is the Turkish version of Danish DANBIO rheumatological database which has been established in 2011. We studied RA patients in TURKBIO registry cohort between the dates of 2011 and 2020. All patients fulfilled the American College of Rheumatology criteria for RA and were classified into two groups based on their age at symptom onset: adult-onset RA(>18-<60 years; AORA) and LORA(≥60 years). In both groups, demographical, clinical and laboratory variables; disease activity, current and previous treatment were compared. Results: From 10 centers, 2111 RA patients recruited, and 8.8% of them was LORA patients. In LORA, the frequency of female was less than AORA. While, there was no difference between LORA and AORA in terms of erosion presence and RF positivity, antiCCP positivity was more frequent in LORA group. The use of antiTNF was lower, and the use of rituximab was more frequent in LORA. At 12 months after bDMARDs therapy, serum CRP and ESR levels and DAS28-CRP showed higher changes compared to baseline values in LORA. Although the mortality rate was higher in LORA, the adverse reactions were reported to be higher in AORA, and most common advers reaction was infections in both groups(Table). The longest survival was observed in infliximab and rituximab(median 22 and 20months) in LORA, in rituximab and golimumab(median 16 and 12months) in AORA. Conclusion: The frequency of LORA who uses bDMARDs was 8.8% in our database. In the elderly patient population, there are some reservations about the use of biological drugs in general due to several co-morbidities and concommitant drug used. Although data on this issue are limited, appropriate biological use can be effective and reliable in required patients. References: [1]Zulfigar AA, Niazi R, Pennaforte JL, Andres E. Late-onset rheumatoid arthritis: clinical, biyological, and therapeutic features about a retrospecttive study. Geriatr Psychol Neuropsychiatr Viell 2019;17:51-62 Acknowledgments: None Disclosure of Interests: None declared